Pengaruh Suku Bunga (Bi Rate), Harga Emas Dunia, Tingkat Inflasi, Jumlah Uang Beredar (M2) Dan Harga Minyak Dunia Terhadap Indeks Harga Sahamjakarta Islamic Index (Jii) Di Bursa Efek Indonesia Periode Januari 2008- Desember 2015 - Insiyah, Jauhar, Dr. Didit Purnomo, SE,M.Si, Nurul Huda, S.Ag, M.Ag (2017)
The purposes of this research was to analyze the influence of BI Rate, World Gold Price, Inflation, Money Supply (M2), World Oil Prices on Stock Price Index Jakarta Islamic Index (JII) and how much influence given by each variable on price index JII stocks. By using secondary data (time seriest) monthly from January 2008 to December 2015. The analysis method used is Ordinary Least Square (OLS) while the model will be estimased by analysis Partial Adjustment Model (PAM) and Classical Assumption Test were processed using Quantitative Micro Software E- views version 8.0.0.1. From Classical Assumption Test results conducted this study passed all tests except the multicolinierity test. This study shows there are significant simultaneously BI Rate, the world gold price, inflation, money supply, world oil prices to the price index JII. Partially three macroeconomic variables that significantly influence the stock price index JII, ie inflation, which has a significant negative influence, money supply (M2) and world oil prices have a significant positive effect.